Strengthening Commercial Courts and Departments in Bosnia and Herzegovina : Caseload Distribution, Backlog, and Other Organizational Issues Affecting Performance - World Bank (World Bank, Washington, DC, 2020)
This Report presents the findings of an analysis of selected organizational issues affecting commercial justice performance in Bosnia and Herzegovina (BiH). It is the main deliverable under Component 1 of the BiH Commercial Justice Technical Assistance Project financed by the UK Good Governance and Investment Climate Reform Trust Fund. The Project aims to support justice institutions in implementing reforms that improve efficiency and access to commercial justice in BiH. The Report’s primary focus is workload distribution among commercial courts and departments, and the effect of any imbalances within it on their performance. Other issues covered include: BiH’s caselaw database; its judicial performance evaluation system; production quotas and other incentive systems; its backlog reduction program; and court organization and management. The mixed methodology used to address these topics combined analysis of case flow statistics provided by the BiH High Judicial and Prosecutorial Council (HJPC) with interviews, document review, observation, and comparative experiences.